Analysis of Green Training on Green Employee Performance With Green Behavior as a Mediating Variable in Employees of PT Charoend Pokhpand Jaya Farm - Fauzi, Hamdi Waslan; Ramdan, Asep Muhamad; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of Green Training on Green Employee Performance with Green Behavior as a mediating variable on employees of PT. Charoen Pokphand Jaya Farm. The phenomenon of environmental pollution and hazardous waste (B3) in the industrial sector underlies the importance of implementing the principles of Green Human Resource Management (GHRM), especially environmentally friendly training (Green Training) which can form pro-environmental behavior (Green Behavior) and improve the performance of environmentally aware employees (Green Employee Performance). This study uses a quantitative approach with a survey method and data collection through questionnaires distributed to 68 employees selected by simple random sampling. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that Green Training had a positive and significant effect on Green Behavior and Green Employee Performance. In addition, Green Behavior was proven to significantly mediate the effect of Green Training on Green Employee Performance. These findings highlight the importance of environmentally friendly training in fostering employee behavior and performance that supports corporate sustainability.